Hyponatraemia in a Lao paediatric intensive care unit: Prevalence, associations and intravenous fluid use. (13th October 2018) - Elliman, Mark G; Vongxay, Oulaivanh; Soumphonphakdy, Bandith; Gray, Amy
Abstract : Aim: Hyponatraemia is a common and potentially deadly complication affecting hospitalised children world‐wide. Hypotonic intravenous fluids can be a significant exacerbating factor. Exclusive use of isotonic fluids, coupled with rigorous blood monitoring, has proven effective in reducing hyponatraemia in developed settings. In developing countries, where hyponatraemia is often more common and severe, different factors may contribute to its incidence and detection. We aimed to determine the prevalence and disease associations of hyponatraemia and describe the intravenous maintenance fluid prescribing practices in a Lao paediatric intensive care unit. Methods: We conducted a cross‐sectional study of 164 children aged 1 month to 15 years admitted to intensive care at a tertiary centre in Lao People's Democratic Republic (PDR) and recorded their serum sodium and clinical data at admission and on two subsequent days. Results: Hyponatraemia was detected in 41% (67/164, confidence interval 34–48%) of children, the majority of which was mild (34%, 56/164) and present at admission (35%, 55/158). Hyponatraemia was more common in malnourished children (odds ratio (OR) 2.3, P = 0.012) and females (OR 1.9, P = 0.045). Hyponatraemia correlated with death or expected death after discharge (OR 2.2, P = 0.015); 88% received maintenance intravenous fluids, with 67% of those receiving a hypotonic solution. Electrolyte testing was only performed in 20% (9/46) of patients outside the study protocol. Conclusions: Hyponatraemia is highly prevalent in critically ill children in Lao PDR, as is the continued use of hypotonic intravenous fluids. With financial and practical barriers to safely detecting and monitoring electrolyte disorders in this setting, this local audit can help promote testing and has already encouraged changes to fluid prescribing.